THE ROLE OF MODERN AND TRADITIONAL ACTIVITIES IN TEACHING GRAMMAR - Mirzayeva Sarvinoz Abdukarim qizi; Мirzayeva Маhbuba Mamajonovna (Journal of Innovation in Education and Social Research, 2023)
Language plays an important role in communication, and grammar is the main important element for any language, because the formation of sentences depends primarily on the structure of its sentences. Without grammar, we cannot imagine a sentence. Therefore, grammar is needed for all languages to construct correct sentences. When the grammar is correct, the sentences of the language make sense.